Effect of oxidation on amine-based pharmaceutical degradation and N-Nitrosodimethylamine formation. (15th December 2015) - Wang, Xiaofeng; Yang, Hongwei; Zhou, Beihai; Wang, Xiaomao; Xie, Yuefeng
Abstract: Four pharmaceuticals (ranitidine, nizatidine, doxylamine, and carbinoxamine) were selected as model compounds to assess the efficiency of four oxidants (ozone (O3 ), chlorine (Cl2 ), chlorine dioxide (ClO2 ) and potassium permanganate (KMnO4 )) on the removal of amine-based pharmaceutical and personal care products (PPCPs), as well as the reduction of their N-Nitrosodimethylamine formation potentials (NDMAFPs). The changes in PPCPs and their NDMAFPs during oxidation were quantified using various oxidants and dosages. The relationship between oxidation product structures and NDMAFP changes was also analyzed. The results showed that oxidation with O3, Cl2 and ClO2 were effective in removing the selected PPCPs. However, only ozonation was effective in reducing their NDMAFPs. Ozonation at 6 mg/L removed approximately 90% PPCPs and 90% NDMAFPs for all PPCPs. In addition, the results indicated that ozonation products made little contribution to NDMAFPs. In contrast, some PPCP products had higher NDMAFPs than PPCPs after oxidation with Cl2, ClO2 and KMnO4. There were two possible reaction pathways that led to decrease in NDMAFPs after oxidation. One was oxygen transfer to nitrogen at the tertiary amine site and the other was N-dealkylation from the tertiary amine site. Graphical abstract: Highlights: Compared the effect of controlling PPCP and NDMA by O3, Cl2, ClO2 and KMnO4 oxidation. Oxidation with O3, Cl2 and ClO2 were effective in removing amine-based PPCPs. O3 was the best oxidant in reducing NDMA formation. Oxygen transfer and dealkylation at tertiary site were the reasons for NDMAFP decrease. Some products after Cl2 or ClO2 oxidation had higher NDMAFPs than PPCP itself.